MRI‐based strain measurements reflect morphological changes following myocardial infarction: A study on the UK Biobank cohort. Issue 1 (9th December 2022) - Mansell, Doyin S.; Sammut, Eva; Bruno, Vito D.; Ascione, Raimondo; Rodrigues, Jonathan C. L.; Gill, Harinderjit S.; Fraser, Katharine H.; Cookson, Andrew N.
Abstract: In a porcine experimental model of myocardial infarction, a localised, layer‐specific, circumferential left ventricular strain metric has been shown to indicate chronic changes in ventricular function post‐infarction more strongly than ejection fraction. This novel strain metric might therefore provide useful prognostic information clinically. In this study, existing clinical volume indices, global strains, and the novel, layer‐specific strain were calculated for a large human cohort to assess variations in ventricular function and morphology with age, sex, and health status. Imaging and health data from the UK Biobank were obtained, including healthy volunteers and those with a history of cardiovascular illness. In total, 710 individuals were analysed and stratified by age, sex and health. Significant differences in all strain metrics were found between healthy and unhealthy populations, as well as between males and females. Significant differences in basal circumferential strain and global circumferential strain were found between healthy males and females, with males having smaller absolute values for both (all p ≤ 0.001). There were significant differences in the functional variables left ventricular ejection fraction, end‐systolic volume, end‐systolic volume index and mid‐ventricular circumferential strain between healthy and unhealthy male cohorts aged 65–74 (all p ≤ 0.001). These results suggest that whilst regional circumferential strains may be useful clinically for assessing cardiovascular health, care must be taken to ensure critical values are indexed correctly to age and sex, due to the differences in these values observed here. Abstract : Boxplot showing statistically significant differences in basal circumferential strains between healthy males and females, particularly for age ranges 45‐54 and 65‐74. Based on an analysis of 710 participants in the UK Biobank, the major findings of this study were that healthy males have lower basal and global circumferential left ventricular strains than healthy females. Comparing healthy to unhealthy participants also found increased mid‐ventricular circumferential strains, lowered ejection fractions, and increased end‐systolic volumes in the unhealthy group, particularly for males aged 65‐74.